Nonequilibrium Solution-Based Assemblies from Bottlebrush Block Copolymers for Drug Delivery - Lee, Jeonghun; Toujani, Chiraz; Tang, Yao; Lee, Rahmi; Cureño Hernandez, Karla E.; Guilliams, Bradley F.; Pochan, Darrin J.; Ramírez-Hernández, Abelardo; Herrera-Alonso, Margarita (ACS nano, 2025)
Kinetic aspects of the self-assembly process of block copolymers are of great interest, as they can direct assembly through specific pathways, yielding nonequilibrium states with complex and unprecedented nanostructures. Assembly kinetics of diblock bottlebrushes was shown to influence the material properties of their solid-state nanostructures, yet little is known regarding their solution-based structures. Herein, we target the nonequilibrium self-assembly of nanoparticles from a zwitterionic diblock bottlebrush consisting of poly(d,l-lactide) and poly(2-methacryloyloxyethyl phosphorylcholine) side-chains. Triggered by a large and rapid change in solvent quality, we examine the resulting nonequilibrium structures (nanoparticles) and their equilibrium analogues (micelles). Using a combination of microscopy and light scattering methods as well as molecular simulations, we gain a microscopic understanding of the experimentally observed differences between the two systems. Compared to micelles, nanoparticles were observed to have a considerably lower aggregation number (accurately predicted by micellar evolution kinetics) and more frustrated core-block packing, along with a lower surface density of hydrophilic chains. Both types of assemblies possessed excellent hemocompatibility and colloidal stability under physiological conditions, concentrated salt solutions, and elevated temperature cycling. Encapsulation of a biopharmaceutics classification system (BCS) class II drug showed superior drug loading capacities and efficiencies for nanoparticles that were not achievable by micelles. In essence, this research provides insight regarding the effects of assembly and stabilization kinetics of zwitterionic bottlebrushes, laying the groundwork for future optimization as a drug delivery platform.